The art of desire [large type] - Montgomery, Selena (Random House Large Print, 2023)
"Trouble comes in threes... One doomed love affair after another has made lovely Alex Walton swear off men. Now, she's determined to try something that maybe she can succeed at: a writing career. Little does she know that a chance meeting with a strikingly handsome stranger, a mysterious obelisk, and a lost kingdom will change her life forever. As Alex is about to discover, truth can be stranger--and far more dangerous--than fiction. ...but true love comes only once. After three years inside a terrorist organization, Phillip Turman is trying to rebuild his life. His first assignment is to pick up Alex Walton, the maid of honor for his best friend's wedding, at the airport. His second is to deal with his instant attraction to her. But his third may be the toughest: to keep Alex out of danger as his past--and her need to know about it--threaten to destroy their future"--